KESALAHAN PESERTA DIDIK MENYELESAIKAN SOAL MATEMATIKA BERDASARKAN TAHAPAN KASTOLAN PADA PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DI KELAS VIII SMPN 3 KEC. PANGKALAN KOTO BARU - Riska Kurniati (Departemen Matematika, 2021)
Error analysis is an important thing to do to found out the mastery of the students' material. This study describe mistakes made by students in problems solving math with straight-line equations after applying the learning model cooperative Numbered Heads Together (NHT). The errors studied were based on error according to the Kastolan stages which included conceptual error, procedural error and technical error. Subjects are students class of VIII.1 SMP Negeri 3 Kec. Pangkalan Koto Baru for the academic year 2021/2022 with six research subjects selected to interview. This type research is pre-experimental and descriptive. Data collection techniq are the method of tests and interview. The validity of data carried out by techniques triangulation, namely comparing the data from interview and tests. Data analysis techniques were of data reduction, data presentation, and data verification. The results showed that the research subjects made (1) conceptual errors in the form of students unable to choose the formula correctly, students were correct in choosing formula but could not apply the formula correctly. The percentage of errors is 60.78%, (2) procedural errors in the form of students not being able to solve the problem to the simplest form so that further steps need to be taken, and the discrepancy of the problem solving steps ordered with the completion steps taken by the students. The percentage of errors is 23.53%, (3) technical errorsof students making mistakes in write and calculations with an error percentage of 15.69%.Keywords— Analysis student errors, Types errors according to Kastolan, Numbered Heads Together cooperative learning mode